PENGARUH PERSEPSI RESIKO, KEGUNAAN, KEPERCAYAAN DAN KEMUDAHAN TERHADAP SIKAP PENGGUNAAN MOBILE BANKING DI KOTA AMBON - Rita J.D. Atarwaman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to empirically examine the effect of perceived risk, usability, trust and convenience on attitudes towards mobile banking usage. banking. The data in this study are primary data obtained from distributing questionnaires directly to 102 people in Ambon city government bank customers. The results of multiple regression stated that the risk perception variable had no effect on attitudes to using mobile banking, the perceived usefulness variable had a significant effect on attitudes to using mobile banking, the perceived trust variable had a significant effect on attitudes towards using mobile banking, and the perceived convenience variable had a significant effect on usage attitudes. mobile banking.